Debt, dignity, and defiance: why Greece went to the brink. Issue 6 (2nd November 2018) - Wolf, Reinhard
Abstract: Early in 2015, the new Greek government, led by the left-wing SYRIZA party, refused to complete the second bailout program and insisted on further debt relief. This defiant stance entails a puzzle for rational-choice explanations that focus on expected economic utility: when SYRIZA came to power, the Greek economy had resumed modest growth, while its foreign creditors had extended debt maturities and hinted at the possibility of more debt restructuring in the future. Hence, there seemed no immediate need to force the issue. Furthermore, it appeared very likely that the incoming administration's demands would be rejected by some of the creditors, each of whom wielded effective veto power. In fact, weeks before the final showdown, George Tsebelis, a leading expert in the field of EU governance, had correctly predicted that Athens was set for a dramatic climb-down. This article argues that the Greek government's bargaining tactics were neither a rational answer to the country's economic predicament nor a necessary response to domestic constraints. Instead, moral emotions and status sentiments played a decisive role. The administration's overconfident defiance was strongly influenced by anger at Greece's alleged humiliation at the hand of its creditors.